2017
DOI: 10.1212/wnl.0000000000003746
|View full text |Cite
|
Sign up to set email alerts
|

MRI-visible perivascular spaces in cerebral amyloid angiopathy and hypertensive arteriopathy

Abstract: Different patterns of MRI-visible EPVS provide insights into the dominant underlying microangiopathy type in patients with spontaneous ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
265
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 238 publications
(280 citation statements)
references
References 36 publications
8
265
3
4
Order By: Relevance
“…On the other hand, in the Alzheimer’s Disease Neuroimaging Initiative (ADNI) study H-EPVS were negatively correlated with the performance in the Mini-Mental State Examination. However, the clinical importance of H-EPVS in cognitive impairment has been poorly studied; in particular, it has been described that in specific conditions as in cerebral amyloid angiopathy, a predominance of EPVS in other locations (ie, CSO) may exist 33. Considering the link between H-EPVS and other markers of cSVD and their potential role in cognition, further studies are needed to assess their clinical implication in diagnosis, prognosis and prevention of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the Alzheimer’s Disease Neuroimaging Initiative (ADNI) study H-EPVS were negatively correlated with the performance in the Mini-Mental State Examination. However, the clinical importance of H-EPVS in cognitive impairment has been poorly studied; in particular, it has been described that in specific conditions as in cerebral amyloid angiopathy, a predominance of EPVS in other locations (ie, CSO) may exist 33. Considering the link between H-EPVS and other markers of cSVD and their potential role in cognition, further studies are needed to assess their clinical implication in diagnosis, prognosis and prevention of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Global measures of each SVD type were defined as: (1) total WMH volume normalized for TIV, (2) EPVS-BG, (3) total number of microbleeds, (4) total number of lacunes, and (5) total SVD burden score (Staals et al, 2014). Lacking an established wholebrain measure of EPVS, EPVS-BG were selected to represent "global" EPVS, given its relevance in vascular pathology such as hypertensive arteriopathy and WMH, as opposed to EPVS-CSO which are more commonly linked to cerebral amyloid angiopathy (CAA) (Charidimou et al, 2017). Measures of cognition were MMSE and ACE-R scores.…”
Section: Variables Included In Analysesmentioning
confidence: 99%
“…Pathological studies have shown that CAA with associated hemorrhagic stroke occurs predominantly in lobar and posterior areas [116,117]. Recently, it has been shown that CAA also correlates with perivascular space enlargement, which affects ISF-and CSF-mediated Aβ clearance [99,118]. Vascular amyloid deposition may disrupt perivascular space drainage via a perturbation in normal arteriolar pulsation [14,48].…”
Section: Caa Pathophysiologymentioning
confidence: 99%
“…Aβ deposition may further impair or block perivascular drainage, leading to dilation of perivascular spaces, not only in the cortical grey matter but also in the underlying white matter, which itself is typically not directly affected by CAA. The enlarged perivascular space can reach several millimeters in diameter and may be visible with appropriate brain imaging [100,118,119].…”
Section: Caa Pathophysiologymentioning
confidence: 99%